TAMI-48. ENGRAFTMENT PHENOTYPES IN PRECLINICAL MODEL SYSTEMS REVEAL A FUNCTIONAL SUBGROUP OF PATIENT TUMORS DEPENDENT ON THE BRAIN TUMOR MICROENVIRONMENT FOR GROWTH. (9th November 2020) - Bayley, Nicholas; Tse, Christopher; Zhu, Henan; Yan, Weihong; Gosa, Laura; Baufeld, Lynn; Ta, Lisa; Prins, Robert; Yong, William; Cloughesy, Timothy; Liau, Linda; Graeber, Thomas; et al.
Abstract: The derivation of model systems from patient tumors is a requisite for reproducible and high throughput translational cancer research. However, not all tumors can form a model and those that do often fail to capture the molecular diversity specific to their cancer. The potential tumor-intrinsic underpinnings remain largely unknown. In gliomas, the brain tumor microenvironment (TME) is increasingly acknowledged as a regulator of tumor proliferation, invasion, and therapy response. The dissimilar environment of in vitro and heterotopic xenograft models could potentially play a role in the limited fidelity of these model systems. Here we established a culture-free workflow and biobank of 144 glioma direct-from-patient orthotopic xenografts (DPDOX) and 51 parallel gliomasphere cultures (GS). Our direct-from-patient workflow enabled the exclusive in vivo establishment of several gliomas – hereafter termed TME-dependent tumors – including low and high grade mtIDH gliomas and histone H3.3 G34 glioblastomas notoriously difficult to culture in vitro . Through molecular profiling of over 75 patient tumors and their matched derivative models, we find that DPDOX tumors preserve a gene expression signature of neural and glial interactions not found in GS and enriched in brain TME-dependent patient tumors. While these patient tumors span a diversity of clinical diagnoses, network-based inferred transcription factor activity suggests that they converge on shared master regulators of self-renewal driving proneural and OPC/NPC-like cellular state enrichment. Integrating multi-omic profiling from TCGA and other publicly available datasets reveals that this expression signature corresponds to a shared DNA methylation signature across disparate epigenetic subgroups. These findings suggest a brain TME dependence in patient tumors across multiple molecular and clinical classifications of glioma which leads to a lack of representation in model systems failing to recapitulate tumor-promoting components of the TME. Further this work provides a resource to guide translational investigations accounting for influences of the model environment.